2022
DOI: 10.32526/ennrj/20/202100164
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Ingestion by Fishes from Jamuna River, Bangladesh

Abstract: Microplastics (MP) have been an evolving global concern by dint of the escalation of plastic pollution in the aquatic environment. However, few data document MP ingestion and accumulation in freshwater fauna as compared to marine organisms. This study investigates the prevalence of MPs in the gastrointestinal tracts (GIT) of 45 individuals belonging to seven commonly found Bangladeshi freshwater fish species with different feeding types (herbivore, carnivore, and omnivore). A total of 81 MP items of varying sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, Parvin et al [44] found no correlation with them based on the Turag and Balu River study. On the other hand, other studies of Bangladesh focusing on the Turag, Buriganga, Brahmaputra, Jamuna, Karnaphuli, and southwestern region have found a significant level of correlation between MP concentration and fish length and weight [45,47,55,61].…”
Section: Physical Structure Of Fish (Length and Weight)mentioning
confidence: 83%
See 1 more Smart Citation
“…However, Parvin et al [44] found no correlation with them based on the Turag and Balu River study. On the other hand, other studies of Bangladesh focusing on the Turag, Buriganga, Brahmaputra, Jamuna, Karnaphuli, and southwestern region have found a significant level of correlation between MP concentration and fish length and weight [45,47,55,61].…”
Section: Physical Structure Of Fish (Length and Weight)mentioning
confidence: 83%
“…In the northern part of Bangladesh, Khan and Setu [55] first investigated the MP contamination in the fish species of the Jamuna River. In this investigation, 76% of the fish sample from the Jamuna River contained MPs contamination, with an average of 1.80 ± 1.65 per total fish.…”
Section: Distribution and Accumulation Of Microplastics (Mps) In Fres...mentioning
confidence: 99%
“…Possible uptakes routes of MPs in sh include confusion with food, accidental ingestion while feeding/drinking, and transfer via the food chain (Roch et al 2020). Marine organisms, ranging from planktivorous invertebrates to mammals, are susceptible to swallowing MPs because of their small size, shape or abundance (Nematollahi et (Khan and Setu 2022). Our study provides baseline data on the status of MPs uptake by shes and will be useful to improve our understanding about potential public health risks, especially for the one fth of the world's population who depend on sh and sheries products as the source of main animal protein.…”
Section: Introductionmentioning
confidence: 96%
“…The incidence of microplastics in the gastrointestinal tracts of 45 individuals belonging to seven widely found Bangladeshi freshwater sh species with various eating habits is investigated in a study (Khan and Setu, 2022). Davidson and Dudas (2016) rst studied the amount of microplastics found in wild and cultured Manila clams (Venerupis philippinarum).…”
Section: Introductionmentioning
confidence: 99%